Las técnicas de información y comunicación y su incidencia en el rendimiento académico de los estudiantes de la escuela fiscal mixta “Dr. Manuel Chávez, parroquia Pucayacu, periodo lectivo 2011-2012 - Tipán Cajas, Leonor Noemi (2012)
The purpose of this work is to make students learn the properly use of new information and communication technologies that allows to emit reflective and concrete facts according to their own criteria. This research seeks to determine through the analysis: technical and experimental, the need for the development and implementation of an educational workshop to promote the appropriate use of new technology and communication information in the Fiscal School "Dr. Manuel Chavez". Several authors state that learning difficulties may be caused by the lack of technological resources in the rural schools of the country. The use of surveys used to identify the learning problems in children show that children do not know the use of virtual windows programs and computers and find it difficult to operate a computer, etc. In order to get information, an analysis of the problem was executed, determining that there are different types and methods to learn by using information and communication technologies, which serve as a methodological guide to improve the academic performance of children and teachers from school through different techniques like typing in Microsoft Word, or Mi Primera Encarta references.